2013
DOI: 10.1016/j.jhin.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Sustained meticillin-resistant Staphylococcus aureus control in a hyper-endemic tertiary acute care hospital with infrastructure challenges in Singapore

Abstract: Successful staged implementation of an MRSA bundle in a hyper-endemic setting is sustainable and represents a model that may be adapted for similar settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…Evaluation of the evidence from 13 studies (11 noncontrolled before-after [39][40][41][42][43][44][45][46][47][48][49], one interrupted time series [50] and one qualitative study [51]) showed that a hospital-based surveillance system, especially when linked to national surveillance networks, is associated with a decrease in overall HAI, central line-associated bloodstream infections, ventilator-associated pneumonia, surgical site infection, and catheter-related urinary tract infections. The studies also emphasized that the timely feedback of results is influential in the implementation of effective IPC actions.…”
Section: (Strong Recommendation Very Low Quality Of Evidence)mentioning
confidence: 99%
See 3 more Smart Citations
“…Evaluation of the evidence from 13 studies (11 noncontrolled before-after [39][40][41][42][43][44][45][46][47][48][49], one interrupted time series [50] and one qualitative study [51]) showed that a hospital-based surveillance system, especially when linked to national surveillance networks, is associated with a decrease in overall HAI, central line-associated bloodstream infections, ventilator-associated pneumonia, surgical site infection, and catheter-related urinary tract infections. The studies also emphasized that the timely feedback of results is influential in the implementation of effective IPC actions.…”
Section: (Strong Recommendation Very Low Quality Of Evidence)mentioning
confidence: 99%
“…The studies also emphasized that the timely feedback of results is influential in the implementation of effective IPC actions. Active surveillance with public feedback as part of a methicillin-resistant Staphylococcus aureus (MRSA) care bundle strategy was associated with a decrease in MRSA infections in a hospital in Singapore [50]. One qualitative study explored the importance of surveillance and feedback to stakeholders and found that they were very influential in the implementation of an IPC programme targeting ventilator-associated pneumonia [51].…”
Section: (Strong Recommendation Very Low Quality Of Evidence)mentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, a decreasing trend in MRSA bacteremia has been seen since 2006 in UK, following a government initiative to establish a mandatory surveillance and a target to reduce MRSA bacteremia rates over a 3-year period [5], facilitated by the corresponding optimization of administrative support, infrastructural change and resource allocation [1].…”
Section: Introductionmentioning
confidence: 99%